Effect of the Hemochromatosis Mutations on Iron Overload among the Indian β Thalassemia Carriers. Issue 3 (26th August 2016) - Nadkarni, Anita H.; Singh, Aradhana A.; Colaco, Stacy; Hariharan, Priya; Colah, Roshan B.; Ghosh, Kanjaksha
Abstract : Background: Hereditary hemochromatosis is a disorder of iron metabolism characterized by increased iron absorption.HFE gene mutations C282Y and H63D are responsible for the majority of hereditary hemochromatosis cases. Methods: We tried to look at the effect of HFE mutations on the iron status. A total of 100 β thalassemia traits (BTT) with 100 normal individuals were screened for the C282Y and H63D mutations using PCR‐RFLP. The serum ferritin levels were determined using ELISA kit. Results: We did not find the C282Y mutation in our study group. The allelic frequencies for H63D mutation did not differ significantly between β‐thalassemia traits (8.5%) and normal controls (9%). ΒΤΤ with H63D genotype of H/D (143.16 ± 80.3 ng/ml) and D/D (504 ng/ml) showed higher ferritin levels as against H/H genotype (88.64 ± 92.43 ng/ml). The statistically significant difference was observed in the mean serum ferritin levels among the individuals showing H/H and D/D genotypes ( P < 0.002) and H/D and D/D genotype ( P < 0.01) in both the groups. Conclusion: This suggests that iron load in BTT tends to aggravated with the co‐inheritance of the H63D mutation. The mutant H63D gene showed the presence of haplotype 6 which is reported in the European population suggesting a common origin.